2021
DOI: 10.1088/1361-651x/abe925
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of atomic structure, stability and electronic structure of TaB2/SiC interface

Abstract: The atomic structure, interface stability and electronic interaction of TaB2(0001)/SiC(111) interfaces were investigated by first principles calculation. The study found that the termination atom and stacking position are the key factors affecting the bonding strength and stability of the interface. On the basis of considering work of adhesion (W ad) and interfacial energy (γ int), the Ta–TaB2/C–SiC center-site stacked (Ta–CS–C) and B–TaB2/C–SiC center-site stacked (B–CS–C) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The cut-off energy and k-points convergence tests were performed by optimizing the HfB 2 unit cell (space group: P6/mmm). A cutoff energy of 350 eV and Monkhorst-Pack grid k-points of 9 × 9 × 7 was employed for bulk HfB 2 , according to the convergence test method illustrated in our previous study [22]. The calculated HfB 2 lattice constant of a = 3.165 Å and c = 3.504 Å are consistent with the experimental results (a = 3.14 Å and c = 3.47 Å [23]) and other theoretical results [24,25].…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut-off energy and k-points convergence tests were performed by optimizing the HfB 2 unit cell (space group: P6/mmm). A cutoff energy of 350 eV and Monkhorst-Pack grid k-points of 9 × 9 × 7 was employed for bulk HfB 2 , according to the convergence test method illustrated in our previous study [22]. The calculated HfB 2 lattice constant of a = 3.165 Å and c = 3.504 Å are consistent with the experimental results (a = 3.14 Å and c = 3.47 Å [23]) and other theoretical results [24,25].…”
Section: Computational Detailsmentioning
confidence: 99%
“…In order to distinguish the slab with different terminated atoms, the naming convention is as follows: (0001) slab with Hf and B atom terminations are labeled as: Hf-(0001) and B-(0001), respectively. ( 10 The convergence tests of (0001), (10 10), and (11 20) slab thickness are conducted using the method mentioned in our previous study [22], and the result proved that a 11-layer Hf-(0001), 11-layer B-(0001), 11-layer Hf-B-(10 10), 13-layer B-B-(10 10), 13-layer B-Hf-(10 10), and 12-layer (11 20) slab with a vacuum layer of 20 Å are sufficient to avoid interaction between surfaces of neighboring slabs, and yielded well-converged results. Oxygen molecule is also optimized in a 10 × 10 × 10 box, and the optimized bond length is 1.239 Å, which is basically consistent with those reported in the literature [31].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Haplo‐insufficiency of the TGFβ‐activated kinase 1 binding protein 2 ( TAB2 ) gene was first associated with congenital heart defects (Thienpont et al, 2010) and cardiomyopathy (Cheng et al, 2021). Gradually, the phenotype broadened in some cases to include short stature, facial dysmorphisms, connective tissue abnormalities, and developmental delay (Cheng et al, 2021; Engwerda et al, 2021; Ritelli et al, 2018). A recent study summarizing 70 individuals with TAB2 haplo‐insufficiency showed that cardiac disease, short stature, and hypermobility are the primary characteristics (Engwerda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%